2006
DOI: 10.1007/s10600-006-0120-8
|View full text |Cite
|
Sign up to set email alerts
|

High performance liquid chromatographic analysis of some flavonoids of Ballota species

Abstract: 547.972Ballota L. is a plant belonging to the Lamiaceae family and is represented by 16 taxa in Turkey [1]. Ballota species have been used in Turkish folk medicine as an antiulcer, antispasmodic, diuretic, choleretic, antihaemorrhoidal, and sedative agents [2,3]. The antimicrobial activities [4] and the antioxidant activities [5] of all Ballota species growing in Turkey was recently reported as well as the antifungal activities of some flavonoids isolated from B. glandulossima [6] and B. inaequidens [7]. The w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
(18 reference statements)
0
7
0
Order By: Relevance
“…The inhibition activity was higher for the latter enzyme (IC 50 22.3, 17.5 and 14.2 µM, respectively) than for the former (IC 50 38.5, 47.2, and 103.7 µM) [112]. These enzymatic systems were also the targets of another similar work concerning the isolation of 6 clerodane tricyclic diterpenes from the chloroform extract of B. limbata [107]: ballatenolide A (59), 15-methoxypatagonic acid (71), patagonic acid (72), and limbatenolides A-C (54)(55)(56). All of the compounds showed inhibitory activity with BChE with IC 50 values ranging from 24.9 to 51.0 µM, lower than the standard inhibitor galanthamine (8.5 µM).…”
Section: Enzymatic Activity Modulationmentioning
confidence: 99%
See 1 more Smart Citation
“…The inhibition activity was higher for the latter enzyme (IC 50 22.3, 17.5 and 14.2 µM, respectively) than for the former (IC 50 38.5, 47.2, and 103.7 µM) [112]. These enzymatic systems were also the targets of another similar work concerning the isolation of 6 clerodane tricyclic diterpenes from the chloroform extract of B. limbata [107]: ballatenolide A (59), 15-methoxypatagonic acid (71), patagonic acid (72), and limbatenolides A-C (54)(55)(56). All of the compounds showed inhibitory activity with BChE with IC 50 values ranging from 24.9 to 51.0 µM, lower than the standard inhibitor galanthamine (8.5 µM).…”
Section: Enzymatic Activity Modulationmentioning
confidence: 99%
“…antalyensis, B. cristata, B. larendana, B. saxatilis subsp. brachyodonta[72,73], B. aucheri[74], B. inaequidens[72,73,75,76], B. lanata[77], B. nigra[70], B. nigra subsp. foetida[72,73,78], B. pseudodictamnus[79], B. rupestris[70,78], B. saxatilis[72,73, 80], B. undulata[81], O. fruticosa[82]…”
mentioning
confidence: 99%
“…Labdane diterpenes Ballonigrin, dehydrohispanolone (hispanone) 11,12 18-hydroxyballonigrin 13 Flavones Apigenin 14,15 Ladanein 12…”
Section: Phytochemicals Namementioning
confidence: 99%
“…It has been reported that 33 to 35 species exist in the genus Ballota that are mainly distributed around the Mediterranean and Eurasia (6,7). Ballota species have been widely used in traditional medicine as sedative, antispasmodic, diuretic, choleretic, and antihemorrhoidal agents (8). Several compounds have been reported in B. nigra, including terpenes, flavonoids, phenylpropanoids, and tannins (9).…”
Section: Introductionmentioning
confidence: 99%